New aspects of p66Shc in ischaemia reperfusion injury and other cardiovascular diseases. (14th April 2016) - Di Lisa, Fabio; Giorgio, Marco; Ferdinandy, Peter; Schulz, Rainer
Abstract : Although reactive oxygen species (ROS) act as crucial factors in the onset and progression of a wide array of diseases, they are also involved in numerous signalling pathways related to cell metabolism, growth and survival. ROS are produced at various cellular sites, and it is generally agreed that mitochondria generate the largest amount, especially those in cardiomyocytes. However, the identification of the most relevant sites within mitochondria, the interaction among the various sources, and the events responsible for the increase in ROS formation under pathological conditions are still highly debated, and far from being clarified. Here, we review the information linking the adaptor protein p66Shc with cardiac injury induced by ischaemia and reperfusion (I/R), including the contribution of risk factors, such as metabolic syndrome and ageing. In response to several stimuli, p66Shc migrates into mitochondria where it catalyses electron transfer from cytochrome c to oxygen resulting in hydrogen peroxide formation. Deletion of p66Shc has been shown to reduce I/R injury as well as vascular abnormalities associated with diabetes and ageing. However, p66Shc‐induced ROS formation is also involved in insulin signalling and might contribute to self‐endogenous defenses against mild I/R injury. In addition to its role in physiological and pathological conditions, we discuss compounds and conditions that can modulate the expression and activity of p66Shc. Linked Articles: This article is part of a themed section on Redox Biology and Oxidative Stress in Health and Disease. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v174.12/issuetoc